Effect of saffron aqueous extract during resistance training on the expression of fibronectin type III domain-containing protein 5 in the hippocampus of rats with type 2 diabetes - Farzad Baratyan; Vahid Valipour dehnou; Amir Khosravi (Complementary Medicine Journal of Faculty of Nursing and Midwifery)
Introduction: It has been demonstrated that fibronectin type III domain-containing protein 5 (FNDC5) improves cognitive function by increasing neurotrophic factors. Furthermore, type 2 diabetes causes a decrease in cognitive function. The combined effect of saffron extract and resistance training on FNDC5 protein levels in rats with type 2 diabetes has not been investigated so far. Therefore, the present study aimed to assess the effect of saffron extract consumption during resistance training on FNDC5 protein expression in the hippocampus of rats with type 2 diabetes. Methods: In this experimental study, 30 adult male rats were randomly assigned to five groups: control (C), diabetes (D), diabetes-resistance training (DT), diabetes-saffron extract (DS), and diabetes-saffron extract-resistance training (DTS). Resistance training was performed in five sessions a week for six weeks. Blood glucose levels and hippocampus FNDC5 protein levels were measured. To analyze the data, one-way ANOVA with Tukey's post hoc test was used at the significance level of P < 0.05. Results: The blood glucose levels of all groups were significantly higher than the C group (P=0.001). Blood glucose levels were significantly lower in the DT, DS, and DTS groups than in the D group (P=0.001). Moreover, in the DTS group, the blood glucose levels were significantly lower than those in the DT group (P=0.014). FNDC5 protein levels were significantly lower in all groups than in the C group (P<0.05). In addition, FNDC5 protein levels of the D and DS groups were significantly lower than the DTS group (P<0.05). Nonetheless, the FNDC5 protein levels of the D and DS groups did not differ significantly (P=0.92); however, the FNDC5 protein levels of the D and DT groups displayed a significant difference (P=0.006). Conclusion: Resistance training and the consumption of saffron extract alone and in combination with each other can reduce blood glucose levels in rats with type 2 diabetes. Nevertheless, the consumption of saffron extract did not increase FNDC5 protein levels. However, resistance training alone and together with saffron consumption increased FNDC5 protein levels. Therefore, in order to control blood glucose levels and increase FNDC5 protein levels, it is suggested that saffron be consumed during resistance training in rats with type 2 diabetes.